2022
DOI: 10.2967/jnumed.122.264689
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast-Activation Protein PET and Histopathology in a Single-Center Database of 324 Patients and 21 Tumor Entities

Abstract: We present an overview of our prospective fibroblast-activation protein inhibitor (FAPI) registry study across a 3-y period, with head-tohead comparison of tumor uptake in 68 Ga-FAPI and 18 F-FDG PET, as well as FAP immunohistochemistry. Methods: This is an interim analysis of the ongoing 68 Ga-FAPI PET prospective observational trial at our department. Patients who underwent clinical imaging with 68 Ga-FAPI PET between October 2018 and October 2021 were included. Tracer uptake was quantified by SUV max for tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(11 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…The communication is complicated between tumor metabolism and heterogeneous stromal components in the tumor microenvironment. Previous studies showed that 68 Ga-FAPI PET uptake and distribution strongly correlated with FAP expression characterized by immunohistochemistry in tumor tissues (10,16). FAP-positive cancerassociated fibroblast subsets contribute to immunosuppression through multiple pathways, including assisting differentiation of monocytes to M2-like macrophages, secreting chemokine (C-X-C motif) ligand 12, enhancing recruitment of myeloid-derived suppressor cells, and promoting generation of regulatory T cells (17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 96%
“…The communication is complicated between tumor metabolism and heterogeneous stromal components in the tumor microenvironment. Previous studies showed that 68 Ga-FAPI PET uptake and distribution strongly correlated with FAP expression characterized by immunohistochemistry in tumor tissues (10,16). FAP-positive cancerassociated fibroblast subsets contribute to immunosuppression through multiple pathways, including assisting differentiation of monocytes to M2-like macrophages, secreting chemokine (C-X-C motif) ligand 12, enhancing recruitment of myeloid-derived suppressor cells, and promoting generation of regulatory T cells (17)(18)(19)(20).…”
Section: Discussionmentioning
confidence: 96%
“…FAP is expressed in a wide range of tumor types, making it a promising target for cancer imaging and radionuclide therapy in recent years ( 4 , 5 ). Apart from neuroendocrine tumors, most other cancers, such as NPC, thyroid cancer, and breast cancer, express SSTR2 ( 9 , 14 , 22 , 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…The quinoline-based small molecule inhibitors that target FAP, known as FAPIs (including FAPI-04 [6,11], FAPI-46 [12,13], and FAPI-74 [14,15]), labeled with 68 Ga for use in positron emission tomography (PET) scans, have exhibited promising outcomes in the diagnosis of various types of cancers [15][16][17]. These tracers exhibit a high a nity for FAP and demonstrate enhanced selectivity towards tumors compared to normal tissues.…”
Section: Introductionmentioning
confidence: 99%